Effect of High Dose of Soybean Meal on the Histology and Function of the Thyroid Gland in Albino Rat at Pre- and Postpuberty - Abdul-Ridha, Siham M.; H. Baraaj, Abed; R. Hamudi, Salim (Iraqi Journal of Science, 2023)
The study aimed to determine the effect of soybean meal on the histologicalstructure and some functional parameters of the thyroid gland was investigated inthis study. For this purpose, 24 white male rats were divided into four groups eachof six rats, as following (G1): normal control rats, at the prepubertal life stage, weredissected after 40 days from the weaning (i.e., from Postnatal Day "PND" 21),(G2): prepubertal rats, were treated with high dose of soybean meal "40% of dailydiet" for 40 days after the weaning, (G3): normal control rats, at the postpubertalstage, were dissected after 40 days from the puberty (i.e., from PND 60), (G4):postpubertal rats, were treated with high dose of soybean meal (40%) for 40 daysafter the puberty. Phenotypic, histological and physiological changes wereexamined. The results reported that, consumption of soybean at prepubertydecreased the thyroid activity by the increasing of the cold "inactive" follicles, whileat postpuberty, soybean caused hyperactivity of the thyroid which led to thehyperplasia and hypertrophy, then to the goiter,significant increase in the ratio ofcold follicles in the (G2) and significant decrease in the (G4), significant decrease inthe height of follicular cell in the (G2) and significant increase in the (G4),significant increase in the diameter of follicular lumen in the (G2) and significantdecrease in the (G4). Also, soybean meal caused significant increase in the bodyweight and significant decline in (T3 and T4) hormones levels.From the results ofthe present study, it is concluded that the high doses of the soybean affect adverselythe function and tissue of the thyroid at both life stages, pre and postpuberty.